Rahasia dibalik Strategi Mahasiswa: Cara Kreatif Mengelola Stres di Dunia Perkuliahan - Alifyah Ika Putri; Sindy Nurhaliza; Tasya Rahmatika Basitu (Alahyan Jurnal Pengabdian Masyarakat Multidisiplin, 2025)
Stress is a common issue faced by students in university life. Various challenges, both academic and social, often create psychological pressures that impact students' mental well-being. This study aims to explore the creative strategies employed by students to manage stress during their time in university. A qualitative approach was used, involving in-depth interviews with students from various disciplines and observations of their daily activities. The results of the study show that students frequently rely on several creative methods, such as effective time management, relaxation techniques, involvement in extracurricular activities, and peer support and experience- sharing. Additionally, many students also use personal hobbies or interests, such as arts, sports, and music, to relieve stress. This research suggests the importance of developing creative skills to manage stress and emphasizes the need for strong social support networks among students. The implications of this study highlight the necessity of providing facilities and programs that support students' mental well-being, such as workshops or stress management training that can teach creative techniques for dealing with pressures in university life.